High-conductivity copper-zirconium alloy material and preparation method thereof

By optimizing the proportion and microstructure of Zr and Cr elements, combined with the addition of phosphorus and oxygen, the problem of insufficient conductivity and difficulty in taking into account the strength of high temperature resistance is solved, and copper-zirconium alloy materials with high conductivity and medium tensile strength is realized, which improves charging efficiency.

CN119736516AActive Publication Date: 2025-04-01JINTIAN COPPER GROUP CORP NINGBO
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411949490.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing copper-zirconium alloy materials are insufficient in high-voltage charging devices, and are difficult to take into account both high temperature resistance and strength, resulting in low charging efficiency and poor material performance.

Method used

By controlling the proportion of Zr and Cr elements, the microstructure of copper-zirconium alloys is optimized, including the size and distribution of the primary Zr-containing phase and the precipitated Zr-containing phase, and the reasonable addition of phosphorus and oxygen to improve the conductive properties and strength of the material.

Benefits of technology

The high conductivity (95% IACS or above) and medium tensile strength (410MPa or above) of copper-zirconium alloy materials are achieved, while ensuring the high temperature resistance and strength of the material and improving charging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736516A_ABST
    Figure CN119736516A_ABST
Patent Text Reader

Abstract

The invention discloses a high-conductivity copper-zirconium alloy and a preparation method thereof.The high-conductivity copper-zirconium alloy comprises Cu, doping elements and inevitable impurities, the total mass percent of all the elements is 100%, the doping elements comprise 0.10 wt%-0.20 wt% of Zr, 0.007 wt%-0.015 wt% of P, 0.005 wt%-0.015 wt% of Cr and 8 ppm-20 ppm of O, and the mass percent ratio of Zr to Cr is (15-20): 1. The copper-zirconium alloy has proper strength and relatively high conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a high-conductivity copper-zirconium alloy material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles, automobile charging efficiency is an important indicator for consumers to make decisions. Therefore, the charging voltage of new energy charging platforms continues to increase. High-voltage circuits are prone to arc erosion during the closing process. Secondly, according to Q=U^2 / R*t, it can be seen that the increase in voltage will cause the heat of the charging device to increase exponentially and the temperature to rise sharply. Based on the above situation, the materials required for new energy charging devices currently have high conductivity, high high temperature resistance and high strength.

[0003] Although copper materials currently have high electrical conductivity, they are no longer suitable for high-voltage charging devices due to their insufficient high-temperature resistance. CuZr alloys use copper as the matrix and add an appropriate amount of Zr to the copper alloy. Since Zr has little effect on the conductivity of the material after precipitation in the material, and Zr precipitation in the material forms aging strengthening and a certain amount of work hardening, the CuZr alloy has high electrical conductivity and strength. At present, CuZr alloys can effectively improve tensile strength and high-temperature resistance by increasing the content of other elements such as Zr, but their electrical conductivity is generally <90% IACS.

[0004] The invention patent application with publication number CN111363937A discloses a copper alloy wire for connectors and a manufacturing method thereof. The copper alloy wire includes the following components in mass percentage: silver: 5-15%, zirconium: 0.1-0.9%, rare earth metal: 0.05-0.2%, and the balance is copper; first, silver, copper, copper-zirconium master alloy and rare earth copper master alloy are mixed, smelted and cast, and a copper alloy ingot is obtained by homogenization and mechanical processing. The ingot is hot extruded, cold drawn for multiple times, and then solution treated, and then finely drawn and annealed to prepare the copper alloy wire. The patent application increases the tensile strength of the material to 550MPa by increasing the Zr content and appropriately adding rare earth elements, but the conductivity is only 83% IACS.

[0005] The invention patent application with publication number CN116000084A discloses a method for preparing a high-strength and high-conductivity copper-zirconium alloy wire. The chemical composition of the alloy material is Cu, Zr, O elements and impurity elements, and the weight percentages are: Cu ≥ 99.80%, Zr: 0.10-0.20%; the preparation method of the alloy wire is: batching and smelting → cold forging → hot extrusion → hot rolling → solution treatment and surface treatment → cold drawing → aging treatment and surface strengthening. The patent application claims that after increasing the solution temperature and applying a strengthening agent to dry, the material tensile strength can reach more than 540MPa, but the conductivity is only 81-83% IACS.

[0006] For high-voltage charging devices, moderate strength is sufficient. The most important thing is how to improve the charging efficiency. To improve the charging efficiency, it is necessary to further improve the conductivity of existing materials. Therefore, it is urgent to design a copper-zirconium alloy with moderate strength and high conductivity. Summary of the invention

[0007] The invention provides a copper-zirconium alloy material with suitable strength and high electrical conductivity.

[0008] The invention provides a high-conductivity copper-zirconium alloy, comprising Cu, doping elements and inevitable impurities, wherein the total mass percentage of all elements is 100%, wherein the doping elements include Zr: 0.10-0.20wt%, P: 0.007-0.015wt%, Cr: 0.005-0.015wt%, O: 8-20ppm, and the mass percentage of Zr and Cr is (15-20):1.

[0009] The functions of the doping elements provided by the present invention are as follows:

[0010] Zirconium: The precipitation of zirconium in the material is beneficial to improving the strength and hardness of the material, and the more complete the precipitation, the less impact it has on the conductivity of the material. Therefore, the appropriate Zr content in the material preparation process and the promotion of sufficient Zr precipitation are beneficial to enhancing the strength of the material while improving the conductivity of the material.

[0011] Oxygen: Excessive oxygen is harmful to the material, but a small amount of oxygen can purify impurities in the copper alloy, which is beneficial to the improvement of the conductivity of the copper alloy. However, when the impurity content is too high, its purification effect will lose its meaning. Copper-zirconium alloy has fewer impurities inside, so a small amount of oxygen content is beneficial to improving the conductivity of the material. Secondly, the remaining small amount of oxygen is pinned to the grain boundary in the form of interstitial atoms, which is beneficial to the improvement of the material strength.

[0012] Phosphorus: Phosphorus is the most effective and lowest cost deoxidizer, which is beneficial to control the oxygen content in the alloy. 3P phase can improve the high temperature plasticity of copper alloy, make it show better plastic deformation ability in high temperature environment, and avoid defects in the production process that affect material properties. Since phosphorus has a certain solid solubility in copper, and phosphorus dissolved in copper significantly reduces its conductivity, in order to ensure the conductivity of copper alloy, the phosphorus content needs to be controlled.

[0013] Chromium: When the Cr content in the material is lower than the solid solubility, the Cr in the material will still have a tendency to precipitate, thus forming a Cr-rich zone, and the Zr element has a certain inhibitory effect on the precipitation of Cr. Therefore, Cr is beneficial to control the size of the initial Zr phase. However, when the Cr content is higher than the solid solubility, the Cr in the material will precipitate, thereby occupying the nucleation position of Zr, inhibiting the subsequent precipitation of Zr, resulting in insufficient Zr precipitation during the aging process, thereby causing the conductivity of the material to decrease.

[0014] Preferably, the main strengthening phases of the copper-zirconium alloy material are primary Zr-containing phase, precipitated Zr-containing phase, Cr-rich solid solution phase and CuP intermetallic compound, wherein the average size of the primary Zr-containing phase is less than 2 μm, the average size of the precipitated Zr-containing phase is less than 1 μm, and the ratio of the primary Zr-containing phase to the precipitated Zr-containing phase is 1:10-15.

[0015] The present invention controls the size of the primary Zr-containing phase and the precipitated Zr-containing phase, shortens the distance between the strengthening phases, and makes the copper-zirconium alloy provided by the present invention have suitable strength. The present invention further controls the content of the precipitated Zr-containing phase, so that the content of the precipitated Zr-containing phase is in a higher range, thereby the Zr phase dissolved in the matrix is ​​at a lower level, and the copper-zirconium alloy provided by the present invention has higher electrical conductivity.

[0016] Preferably, the primary Zr-containing phase is elliptical. The elliptical primary Zr-containing phase is conducive to the propagation of electrons and improves the electrical conductivity of the copper-zirconium alloy.

[0017] Preferably, the copper-zirconium alloy has a grain size of 0.02-0.04 mm, a conductivity of more than 95% IACS, and a strength of more than 410 MPa.

[0018] On the other hand, the present invention also provides a method for preparing the high-conductivity copper-zirconium alloy, comprising: the process flow of the preparation method comprises: batching and melting → continuous extrusion → solid solution → cold drawing → aging treatment;

[0019] Wherein, the ingredients are mixed and melt-casted according to the percentage of each component of the high-conductivity copper-zirconium alloy;

[0020] The solution temperature T is:

[0021] T=122ln(-30X+0.12)+1195

[0022] Wherein, X is the content of Zr;

[0023] The aging temperature is 400-420°C.

[0024] In copper-zirconium alloy, as more Zr elements are dissolved into copper, the conductivity of the copper alloy becomes lower. After aging, Zr elements will continue to precipitate, thereby reducing the influence of Zr elements on the conductivity of copper. However, in the prior art, the Zr content dissolved into the matrix is ​​increased by increasing the solid solution temperature, and a large number of dislocations are formed by a large processing rate in the later process, thereby providing a large number of nucleation sites for the precipitation of Zr. The more nucleation sites, the smaller and more dispersed the precipitated phase is, thereby improving the strength of the material. However, in the above method, the Zr content dissolved into the matrix is ​​high, so the Zr content is also increased after aging precipitation. Secondly, the precipitated phase is fine, which ultimately leads to low conductivity of the product. Another method in the prior art can promote the growth of the precipitated phase by increasing the aging temperature, but the material strength is seriously reduced while the precipitated phase grows. Because the growth of the precipitated phase is random, the uniformity of the material is deteriorated. In view of the above technical problems, the present invention determines the relationship between the amount of zirconium added in the copper alloy and the solid solution temperature: T = 122ln (-30X + 0.12) + 1195, controls the content of Zr elements dissolved in copper, reduces the solid solution base, so that a large amount of Zr in the matrix can be precipitated in the subsequent aging process, forming a large number of precipitated Zr-containing phases of suitable size, and improving the electrical conductivity. Secondly, the Cr element is added to control the size of the initial Zr phase, so that the initial Zr-containing phase and the aging precipitated Zr-containing phase synergistically reduce the secondary phase spacing in the matrix and strengthen the material. Since the influence of the initial phase in the material on the electrical conductivity is reduced compared to the aging precipitation phase, the material conductivity is improved, and a copper-zirconium alloy with higher electrical conductivity and medium tensile strength is obtained compared to the past.

[0025] Preferably, the single-pass drawing processing amount of the cold drawing is 20-25%, and the total cold drawing processing amount is 60-70%.

[0026] The present invention forms a large number of dislocations through a large processing amount, reduces the nucleation energy of the precipitated Zr-containing phase, increases the nucleation position, and at the same time, under the induced precipitation effect of the initial Zr-containing phase, the Zr element dissolved in the matrix is ​​fully precipitated, reducing the hindering effect of Zr in the matrix on electrons. At the same time, since the initial Zr-containing phase has a certain coherent relationship with the matrix, under the pulling effect of a large processing amount, the initial Zr-containing phase presents an elliptical shape, thereby reducing the obstacle to electron conduction and improving the electrical conductivity.

[0027] Preferably, the solution heat preservation time is 30-60 minutes, and then water cooling is used to cool to room temperature. By controlling the heat preservation time, the blank is heated evenly while avoiding coarse grains caused by the solution time process.

[0028] Preferably, the melting temperature of the molten casting is 1200-1300° C., the pulling speed is 0.6-0.7 mm / s, and argon gas is used for protection during the pulling process to avoid oxidation loss of alloy elements.

[0029] Preferably, P is added in an amount of 0.007%-0.015% during the melting and casting process to improve the high temperature fluidity of the billet and avoid cracking of the billet during casting. The addition of the P element achieves a degassing effect, thereby controlling the O content to 8ppm-20ppm.

[0030] Preferably, the specific steps of melting and casting include:

[0031] Before smelting, copper and zirconium need to be wrapped with copper sheets to prepare cored wires. After smelting begins, an appropriate amount of oxygen-free copper rods are first added to the upper lead furnace, argon gas is introduced and heated. After the oxygen-free copper rods are completely melted, the oxygen-free copper rods and copper-zirconium alloy cored wires are automatically fed, and the feeding speed is controlled at 220 kg / h. Automatic feeding is stopped when the copper liquid is 20 cm away from the edge of the crucible; the final temperature is maintained at 1200-1300°C, and the composition is measured and adjusted after 10-20 minutes of insulation. After the composition is qualified, the upper lead blank is produced. In the subsequent traction process, oxygen-free copper rods and copper-zirconium cored wires (copper-phosphorus and copper-chromium alloys prepared by mixing in proportion) are automatically fed according to the predetermined design composition, and the furnace liquid is tested for composition every 30 minutes to ensure the composition of the upper lead blank, and finally the required upper lead blank is obtained.

[0032] Preferably, the processing amount of the continuous extrusion is 15-20%. The present invention controls the processing amount of continuous pressurization to ensure that the cast structure in the extruded blank is completely broken and the grains before the solution treatment are relatively fine.

[0033] Preferably, the aging insulation time is 4-7h, and the cooling method is furnace cooling.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention controls the ratio of Zr and Cr elements so that a chromium-rich solid solution phase is formed in the matrix, and the size of the initial Zr-containing phase is controlled by utilizing the inhibitory effect of Zr on the precipitation of the chromium-rich solid solution phase, so that the size of the initial Zr-containing phase is smaller, thereby reducing the distance between the initial Zr-containing phase and the precipitated Zr-containing phase, thereby making the copper alloy have appropriate strength; if the Cr element content is too high, Cr will precipitate, thereby occupying the nucleation position of Zr, making Zr precipitation insufficient, resulting in a large amount of Zr in the matrix, thereby hindering electron conduction and affecting electrical conductivity; therefore, the present invention controls the ratio of Zr and Cr elements so that the copper alloy has appropriate strength and high electrical conductivity.

[0036] In the preparation method of the present invention, the solution temperature is controlled based on the relationship between the Zr content and the solution temperature, so that an appropriate amount of Zr is dissolved in the matrix, so that a large amount of Zr precipitation can be achieved at a relatively low aging temperature, thereby reducing the Zr content dissolved in the matrix, improving the electrical conductivity, and ensuring appropriate strength; under the action of the chromium-rich zone formed by a trace amount of Cr, the size of the primary Zr-containing phase is relatively small, and the size of the precipitated Zr-containing phase formed at a relatively low aging temperature is also relatively small. Since the sizes of the primary Zr-containing phase and the precipitated Zr-containing phase are both relatively small, and the precipitated Zr-containing phase is precipitated between the primary Zr-containing phases, the spacing between the strengthening phases is reduced, so that the copper-zirconium alloy provided by the present invention has appropriate strength.

[0037] Instruction Manual

[0038] Figure 1 This is an electron microscope image of the primary phase of the copper-zirconium alloy material prepared in Example 1 of the present invention.

[0039] Figure 2 This is an electron microscope image of the primary phase and precipitated phase of the copper-zirconium alloy material prepared in Example 1 of the present invention.

[0040] Specific embodiment

[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0042] The present invention provides 3 embodiments and 4 comparative examples, and the specific components are shown in Table 1

[0043] The embodiment adopts the preparation method of the present invention for preparation, and the process flow is: raw material preparation → upward continuous casting → continuous extrusion → solution → cold working → aging treatment. The raw materials are: oxygen-free copper rod, copper-zirconium alloy cored wire, and copper-chromium alloy and copper-phosphorus alloy are added to the cored wire in proportion.

[0044] Example 1

[0045] Copper-zirconium alloy, calculated by mass percentage 100%, includes the following components: Zr: 0.10%; P: 0.008%;

[0046] Cr: 0.006%; 0: 10ppm, wherein the content of Zr and Cr is within Zr:Cr=(15-20):1, and the balance is Cu.

[0047] Step 1: Use an upper furnace for smelting and blank preparation, the smelting and insulation temperature is controlled at 1280℃, the pulling speed is controlled at 0.7mm / s, argon protection is used during the pulling process, the cooling water flow rate is controlled at 11m^3 / min, and the cooling water temperature is controlled at 23℃, and finally a qualified upper blank is prepared.

[0048] Step 2: The above-mentioned upper blank is extruded by a continuous extruder, and the extrusion processing amount is controlled at 18.5% to ensure that the cast structure in the extruded blank is completely broken;

[0049] Step 3: The extruded blank is subjected to high-temperature solution treatment. The solution temperature is determined by the zirconium content. The relationship is: T = 122ln (-30X + 0.12) + 1195; solution temperature: 901 ° C, Zr content: 0.10%, that is, X = 0.001. The solution holding time is 40 minutes, and water cooling is quickly used after the end of the holding.

[0050] Step 4: cold drawing the solutionized blank, with the single-pass drawing amount controlled at 20-25% and the total cold drawing amount controlled at 70%;

[0051] Step 5: The drawn blank is subjected to low-temperature aging, the aging temperature is 420°C, the holding time is 5h, and the cooling method is furnace cooling.

[0052] Example 2

[0053] Copper-zirconium alloy, calculated by mass percentage 100%, includes the following components: Zr: 0.15%; P: 0.010%;

[0054] Cr: 0.008%; 0: 15ppm, wherein the content of Zr and Cr is within Zr:Cr=(15-20):1, and the balance is Cu.

[0055] Step 1: Use an upper furnace for smelting and blank preparation, the smelting and insulation temperature is controlled at 1280℃, the pulling speed is controlled at 0.7mm / s, argon protection is used during the pulling process, the cooling water flow rate is controlled at 11m^3 / min, and the cooling water temperature is controlled at 23℃, and finally a qualified upper blank is prepared.

[0056] Step 2: The above-mentioned upper blank is extruded by a continuous extruder, and the extrusion processing amount is controlled at 18.5% to ensure that the cast structure in the extruded blank is completely broken;

[0057] Step 3: The extruded blank is subjected to high-temperature solution treatment. The solution temperature is determined by the zirconium content. The relationship is: T = 122ln (-30X + 0.12) + 1195; solution temperature: 879 ° C, Zr content: 0.15%, that is, X = 0.0015. The solution holding time is 40 minutes, and water cooling is quickly used after the end of the holding.

[0058] Step 4: cold drawing the solutionized blank, with the single-pass drawing amount controlled at 20-25% and the total cold drawing amount controlled at 65%;

[0059] Step 5: The drawn blank is subjected to low-temperature aging, the aging temperature is 420°C, the holding time is 5h, and the cooling method is furnace cooling.

[0060] Example 3

[0061] Copper-zirconium alloy, calculated by mass percentage 100%, includes the following components: Zr: 0.20%; P: 0.007%;

[0062] Cr: 0.011%; 0: 20ppm, wherein the content of Zr and Cr is within Zr:Cr=(15-20):1, and the balance is Cu.

[0063] Step 1: Use an upper furnace for smelting and blank preparation, the smelting and insulation temperature is controlled at 1280℃, the pulling speed is controlled at 0.7mm / s, argon protection is used during the pulling process, the cooling water flow rate is controlled at 11m^3 / min, and the cooling water temperature is controlled at 23℃, and finally a qualified upper blank is prepared.

[0064] Step 2: The above-mentioned upper blank is extruded by a continuous extruder, and the extrusion processing amount is controlled at 18.5% to ensure that the cast structure in the extruded blank is completely broken;

[0065] Step 3: The extruded blank is subjected to high-temperature solution treatment. The solution temperature is determined by the zirconium content. The relationship is: T = 122ln (-30X + 0.12) + 1195; solution temperature: 852 ° C, Zr content: 0.20%, that is, X = 0.002. The solution holding time is 40 minutes, and water cooling is quickly used after the end of the holding.

[0066] Step 4: cold drawing the solutionized blank, with the single-pass drawing amount controlled at 20-25% and the total cold drawing amount controlled at 60%;

[0067] Step 5: The drawn blank is subjected to low-temperature aging, the aging temperature is 420°C, the holding time is 5h, and the cooling method is furnace cooling.

[0068] Comparative Example 1

[0069] Compared with Example 1, the difference is that the solution temperature is 930°C.

[0070] Comparative Example 2

[0071] Compared with Example 2, the difference is that the Cr component is higher, based on 100% by mass, Zr: 0.20%; P: 0.007%; Cr: 0.10%; 0: 20 ppm, and the balance is Cu.

[0072] Comparative Example 3

[0073] Compared with Example 3, the difference is that the P element is higher, based on the mass percentage of 100%, Zr: 0.20%; P: 0.018%; Cr: 0.011%; 0: 20ppm, wherein Zr: Cr = (15-20): 1, and the balance is Cu.

[0074] Comparative Example 4

[0075] Compared with Example 3, the difference is that the elements in step O are relatively high: based on 100% by mass, Zr: 0.20%; P: 0.018%; Cr: 0.011%; O: 50ppm, wherein Zr:Cr=(15-20):1, the remainder is Cu.

[0076] Comparative Example 5

[0077] Compared with Example 2, the difference is that in step 4: the overall processing volume is 50%

[0078] Comparative Example 6

[0079] Compared with Example 2, the difference is that the solution temperature is 930°C, and the aging temperature in step 5 is controlled at 470°C.

[0080] The chemical components of the embodiments and comparative examples are summarized in Table 1; the grain size, second phase size, tensile strength, and electrical conductivity of the copper alloys prepared in the embodiments and comparative examples are tested as shown in Table 2. The specific test methods are as follows:

[0081] Tensile strength: tested in accordance with GB / T228.1-2021 "Tensile test of metallic materials - Part 1: Room temperature test method";

[0082] Conductivity: Tested in accordance with GB / T32791-2016 "Eddy Current Test Method for Electrical Conductivity of Copper and Copper Alloys";

[0083] High temperature softening resistance: tested in accordance with GB / T 33370-2016 "Determination of softening temperature of copper and copper alloys".

[0084] like Figure 1 As shown, the distance between the initial phases is relatively large, which is not conducive to the improvement of material strength. Figure 2 It can be seen that the existence of the precipitated phase can greatly reduce the spacing between the strengthening phases, and the strength of the material is positively correlated with the spacing between the strengthening phases. At the same time, the initial phase has little effect on the electrical conductivity of the material, so that the material has medium-strength and high-conductivity properties.

[0085] Table 1 Comparative Examples and Examples Composition

[0086]

[0087] Table 2 Physical properties of comparative examples and embodiments

[0088]

[0089] As shown in Table 2, under the present invention, by controlling the Zr content dissolved in the matrix, the residual Zr content in the matrix after aging is controlled, so that the products obtained in Examples 1 to 3 have high conductivity; and after aging precipitation, the total number of the initial phase and the precipitated phase is more than 45,000 / mm 2 , thereby ensuring that the product has higher strength; while in the comparative example, by increasing the solid solution temperature and raising the aging temperature, while comparative examples 1 to 6 reduce the amount of cold working and the excessive presence of Cr / P / O elements in the material will lead to a decrease in the conductivity and even the strength of the obtained product, thereby failing to meet the customer's medium-strength and high-conductivity requirements.

Claims

1. A highly conductive copper-zirconium alloy, characterized in that: Including Cu, doping elements and inevitable impurities, the total mass percentage of all elements is 100%, wherein the doping elements include Zr: 0.10-0.20wt%, P: 0.007-0.015wt%, Cr: 0.005-0.015wt%, O: 8-20ppm, and the mass percentage of Zr and Cr is (15-20):

1.

2. The high-conductivity copper-zirconium alloy according to claim 1, characterized in that: The main strengthening phases of the copper-zirconium alloy material are primary Zr-containing phase, precipitated Zr-containing phase, Cr-rich solid solution phase and CuP intermetallic compound, wherein the average size of the primary Zr-containing phase is less than 2 μm, the average size of the precipitated Zr-containing phase is less than 1 μm, and the ratio of the primary Zr-containing phase to the precipitated Zr-containing phase is 1:10-15.

3. The high-conductivity copper-zirconium alloy according to claim 1, characterized in that: The primary Zr-containing phase is elliptical.

4. The high-conductivity copper-zirconium alloy according to claim 1, characterized in that: The copper-zirconium alloy has a grain size of 0.02-0.04 mm, a conductivity of more than 95% IACS, and a strength of more than 410 MPa.

5. A method for preparing a high-conductivity copper-zirconium alloy according to any one of claims 1 to 4, characterized in that: include: The process flow of the preparation method includes: batching and melting → continuous extrusion → solid solution → cold drawing → aging treatment; Wherein, the ingredients are mixed and melt-casted according to the percentage of each component of the high-conductivity copper-zirconium alloy; The temperature T of the solid solution is: T=122ln(-30X+0.12)+1195 Wherein, X is the content of Zr; The aging temperature is 400-420°C.

6. The method for preparing a high-conductivity copper-zirconium alloy according to claim 5, characterized in that: The single-pass drawing processing amount of the cold drawing is 20-25%, and the total cold drawing processing amount is 60-70%.

7. The method for preparing a high-conductivity copper-zirconium alloy according to claim 5, characterized in that: The holding time of the solid solution is 30-60 minutes, and the cooling method is water cooling.

8. The method for preparing a high-conductivity copper-zirconium alloy according to claim 5, characterized in that: P is added in the melting and casting process: 0.007%-0.015% to control the O content to 8ppm-20ppm.

9. The method for preparing a high-conductivity copper-zirconium alloy according to claim 5, characterized in that: The processing amount of the continuous extrusion is 15-20%.

10. The method for preparing a high-conductivity copper-zirconium alloy according to claim 5, characterized in that: The heat preservation time of the aging is 4-7h, and the cooling method is furnace cooling.

Citation Information

Patent Citations

  • Copper alloy wire for inserting piece and manufacturing method of copper alloy wire

    CN111363937A

  • Preparation method of high-strength and high-conductivity copper-zirconium alloy wire

    CN116000084A

  • Multi-scale polybasic high-pressure and high-conductivity copper-chromium-zirconium alloy material and preparation method thereof

    CN109355525A

  • Copper-zirconium alloy plate strip and preparation method thereof

    CN115821106A

  • Easy machining, high strength and high conductive copper alloy

    CN1498978A